2020
DOI: 10.1007/s11033-020-05702-1
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of reactive oxygen species modulator 1 is associated with advanced grades of bladder cancer

Abstract: Reactive Oxygen Species Modulator 1 (ROMO1) plays a pivotal role in the regulation of mitochondrial structure integrity, and the production of reactive oxygen species (ROS). Increased ROMO1 expression was reported in various cancer cell lines; however, the possible association between ROMO1 expression and bladder cancer was not well studied. The present study aimed to investigate the rate of ROMO1 expression and the correlation of oxidative stress with the development of bladder cancer. In this study, a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Recent studies have demonstrated the clinical usefulness of Romo1 gene expression and the novel association between micro RNA and Romo1. Alizamir et al demonstrated that Romo1 mRNA expression increased in bladder cancer tissues and that Romo1 overexpression was associated with advanced tumor (31). Similarly, Afshar et al showed that Romo1 mRNA was overexpressed in gastric cancer tissues and that its overexpression was associated with unfavorable prognosis in patients with gastric cancer (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated the clinical usefulness of Romo1 gene expression and the novel association between micro RNA and Romo1. Alizamir et al demonstrated that Romo1 mRNA expression increased in bladder cancer tissues and that Romo1 overexpression was associated with advanced tumor (31). Similarly, Afshar et al showed that Romo1 mRNA was overexpressed in gastric cancer tissues and that its overexpression was associated with unfavorable prognosis in patients with gastric cancer (32).…”
Section: Discussionmentioning
confidence: 99%
“…Alizamir et al. demonstrated that Romo1 mRNA expression increased in bladder cancer tissues and that Romo1 overexpression was associated with advanced tumor ( 31 ). Similarly, Afshar et al.…”
Section: Discussionmentioning
confidence: 99%
“… 6 7 In 2020, Amini et al 7 conducted a study on ROMO1 and OMA1, and found that overexpression of ROMO1 in gastric cancer tissue promotes oxidative stress in patients with gastric cancer, which is an critical factor in aggravating and even the onset of this deadly cancer. At the same time, in 2020, Ghasemi et al 33 conducted a study on the mitochondrial protein and observed that overexpression of ROMO1 in bladder cancer tissue and also increased ROMO1 in the serum of people with bladder cancer may promote some parameters of oxidative stress in these patients.…”
Section: Covid-19 and Romo1mentioning
confidence: 99%
“…Another point worth noting is that ROMO1 and its association with oxidative stress can affect various organs, particularly the lungs, and it has been observed that ROMO1 might cause some diseases related to this organ, namely lung cancer and some other respiratory diseases. 6 33 In 2017, Lee et al 34 did a study on Lung Cancer-Related Malignant Effusion (LCRME), and observed that ROMO1 in the fluid isolated from the lungs is increased in the malignant state compared with the benign state, then, they introduced ROMO1 as a marker for lung cancer-related malignant effusion. Similarly, in 2020, Kong et al 35 carried out research on poor distant metastasis-free survival in patients with Non-Small Cell Lung Cancer and observed overexpression of ROMO1 in this type of lung disorder.…”
Section: Covid-19 and Romo1mentioning
confidence: 99%
See 1 more Smart Citation